Gentamicin in neonates at risk for sepsis – peak serum concentrations are not necessary - Reynolds, Luke F (Pulsus Group Inc, 2012)
BACKGROUND: Serum gentamicin concentrations (GSCs) are frequently obtained before and after gentamicin administration to newborns with, or at high risk for, sepsis. OBJECTIVE: To determine whether performing a peak GSC assay when the trough GSC is within the guidelines for care would add clinically relevant information for health care workers. METHODS: A retrospective review of the IWK Health Centre (Halifax, Nova Scotia) laboratory database for peak and trough GSC for infants <28 days after birth was performed. RESULTS: Of 5253 paired samples of trough and peak GSCs, 3001 (57%) had trough GSCs ≤2 μg/mL. Of these, only nine (0.3%) had a peak GSC >10 μg/mL. CONCLUSIONS: Performing a peak GSC measurement does not provide further clinically important data and increases patient morbidity and hospital costs.